Application of BigBook Media to Improve Reading Literacy of Grade II Students at SDK Gero - Mawa, Hendriana Audogsia; Sayangan, Yohanes Vianey; Awe, Ermelinda Yosefa; Laksana, Dek Ngurah Laba (Electronic Journal of Education, Social Economics and Technology, 2024)
This research aims to determine the results of media application BigBook in increasing reading literacy in class II students at SDK Gero. The type of research used is classroom action research (PTK). The design of this research uses the Kemmis Mc model. Taggart consists of 4 stages, namely planning, action, observation and reflection.  The subjects in this research were 9 grade II SDK Gero students and the research object was increasing reading literacy through the media BigBook. The data collection methods used in this research are observation, tests and documentation. In this research, a test instrument was used. The test is carried out in the form of a post-test which is carried out during learning on April 29 and 30 2024 using two cycles, namely cycle I and cycle II. The analytical method used in this research is a quantitative data analysis method. Quantitative data is used to determine the results of the posttest with the specified KKM, namely a minimum of 70, while qualitative data is used to analyze the observation sheet. The results showed a significant increase from cycle I to cycle II. In cycle I the average class score was still low with an average of 58.88 and a completion percentage of 11.11%. In the implementation of cycle II the results increased, namely a class average of 78.99 and a completion percentage of 77.77% with an increase in the average class from cycle I to cycle II of 19.67. Media Big Book It can be said to be effective in increasing students' reading literacy and deepening understanding of the content of the texts they read.